Efficacy and Safety of Vagus Nerve Stimulation on Upper Limb Motor Recovery After Stroke. A Systematic Review and Meta-Analysis - Ramos-Castaneda, Jorge A.; Barreto-Cortes, Carlos Federico; Losada-Floriano, Diego; Sanabria-Barrera, Sandra Milena; Silva-Sieger, Federico A.; Garcia, Ronald G. (Frontiers in Neurology, 2022)
Background: Upper limb motor impairment is one of the main complications of stroke, affecting quality of life both for the patient and their family. The aim of this systematic review was to summarize the scientific evidence on the safety and efficacy of Vagus Nerve Stimulation (VNS) on upper limb motor recovery after stroke. Methods: A systematic review and meta-analysis of studies that have evaluated the efficacy or safety of VNS in stroke patients was performed. The primary outcome was upper limb motor recovery. A search of articles published on MEDLINE, CENTRAL, EBSCO and LILACS up to December 2021 was performed, and a meta-analysis was developed to calculate the overall effects. Results: Eight studies evaluating VNS effects on motor function in stroke patients were included, of which 4 used implanted and 4 transcutaneous VNS. It was demonstrated that VNS, together with physical rehabilitation, increased upper limb motor function on average 7.06 points (95%CI 4.96; 9.16) as assessed by the Fugl-Meyer scale. Likewise, this improvement was significantly greater when compared to a control intervention (mean difference 2.48, 95%CI 0.98; 3.98). No deaths or serious adverse events related to the intervention were reported. The most frequent adverse events were dysphonia, dysphagia, nausea, skin redness, dysgeusia and pain related to device implantation. Conclusion: VNS, together with physical rehabilitation, improves upper limb motor function in stroke patients. Additionally, VNS is a safe intervention.